<h3>cos³x - 3cosx - cos2x + 3 = 0</h3>
Применим формулу косинуса двойного аргумента и приведём уравнение к стандартному виду: cos2x = 2cos²x - 1
<h3>cos³x - 3cosx - ( 2cos²x - 1 ) + 3 = 0</h3><h3>cos³x - 3cosx - 2cos²x + 1 + 3 = 0</h3><h3>cos³x - 2cos²x - 3cosx + 4 = 0</h3><h3>Пусть cosx = a , |a| ≤ 1 , тогда </h3><h3>а³ - 2а² - 3а + 4 = 0</h3><h3>а³ - а² - а² + а - 4а + 4 = 0</h3><h3>(а³ - а²) - (а² - а) - (4а - 4) = 0</h3><h3>а²( а - 1 ) - а( а - 1 ) - 4( а - 1 ) = 0</h3><h3>( а - 1 )( а² - а - 4 ) = 0</h3><h3>1) а - 1 = 0 ⇔ а = 1 ⇔ соsx = 1 ⇔ x = 2пn, n ∈ Z</h3><h3>2) a² - a - 4 = 0 </h3><h3>D = (-1)² - 4•(-4) = 1 + 16 = 17</h3><h3>a₁ = ( 1 - √17 )/2 ≈ - 1,5 ⇒ ∅</h3><h3>a₂ = ( 1 + √17 )/2 ≈ 2,5 ⇒ ∅</h3><h3><em><u>ОТВЕТ: 2пn, n ∈ Z</u></em></h3>
10\4 = 2.5 ширина
10 * 2.5 = 25 площадь прямоугольника
1) 9-3=6 6*8=48 стульев
2) 8+2=10 10*9=90 стульев.
3) 9+1=10 10*8=80 стульев.